Does Foreign Exchange Reserve Decumulation Lead to Currency Appreciation? - Kathryn M. E. Dominguez; Rasmus Fatum; Pavel Vacek (University of Copenhagen, Economic Policy Research Unit (EPRU), 2010)
Many developing countries have increased their foreign reserve stocks dramatically in recent years, often motivated by the desire for precautionary self-insurance. One of the negative consequences of large accumulations for these countries is the risk of valuation losses. In this paper we examine the implications of systematic reserve decumulation by the Czech authorities aimed at mitigating valuation losses on euro-denominated assets. The policy was explicitly not intended to influence the value of the koruna relative to the euro. Initially the timing and size of reserve sales was not predictable, eventually sales occurred on a daily basis (in three equal installments within the day). This project examines whether these reserve sales, both during the regime of discretionary timing as well as when sales occurred every day, had unintended consequences for the domestic currency. Our findings using intraday exchange rate data and time-stamped reserve sales indicate that when decumulation occurred every day these sales led to significant appreciation of the koruna. Overall, our results suggest that the manner in which reserve sales are carried out matters for whether reserve decumulation influences the relative value of the domestic currency.
Keywords: E58; F31; F32; F55; 330; foreign exchange reserves; exchange rate determination; high-frequency volatility modeling; Währungsreserven; Wechselkurspolitik; Wechselkurs; Tschechische Republik